(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The article is proposed as a contribution to the critique of the text of Per specula aenigmatis and Cumae by Michele Sovente. After setting a date to two unknown witnesses of the collections, the focus is on one of them, Cumae, which proves to be the editing of 1988 disappeared until today. Therefore, is offered a content description dwelling on possible reprints and variations to finally make some conclusions and philological interpretations.